Pseudomonas aeruginosa Quorum-Sensing and Type VI Secretion System Can Direct Interspecific Coexistence During Evolution - Zhao, Kelei; Du, Lianming; Lin, Jiafu; Yuan, Yang; Wang, Xiwei; Yue, Bisong; Wang, Xinrong; Guo, Yidong; Chu, Yiwen; Zhou, Yingshun (Frontiers in Microbiology, 2018)
It is reported that a wide range of bacterial infections are polymicrobial, and the members in local microcommunity can influence the growth of neighbors through physical and chemical interactions. Pseudomonas aeruginosa is an important opportunistic pathogen normally causes a variety of acute and chronic infections, and clinical evidences suggest that P. aeruginosa can be frequently co-isolated with other pathogens from the patients with chronic infections. However, the interspecific interaction and coexisting mechanism of P. aeruginosa with co-infecting bacterial species during evolution still remain largely unclear. In this study, the relationships of P. aeruginosa with other gram-positive (Staphylococcus aureus) and gram-negative (Klebsiella pneumoniae) are investigated by using a series of on-plate proximity assay, in vitro coevolution assay and RNA-sequencing. We find that although the development of quorum-sensing system contributes P. aeruginosa a significant growth advantage to compete with S. aureus and K. pneumoniae, the quorum-sensing regulation of P. aeruginosa will be decreased during evolution and thus provides a basis for the formation of interspecific coexistence. The results of comparative-transcriptomic analyses suggest that the persistent survival of S. aureus in the microcommunity has no significant effect on the intracellular transcriptional pattern of P. aeruginosa, while a more detailed competition happens between P. aeruginosa and K. pneumoniae. Specifically, the population of P. aeruginosa with decreased quorum-sensing regulation can still restrict the proportion increase of K. pneumoniae by enhancing the type VI secretion system elicited cell aggressivity during further coevolution. These findings provide a general explanation for the formation of dynamic stable microcommunity consisted of more than two bacterial species, and may contribute to the development of population biology and clinical therapy.